2018
DOI: 10.1016/j.bj.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Oral infection of mice with Fusobacterium nucleatum results in macrophage recruitment to the dental pulp and bone resorption

Abstract: BackgroundFusobacterium nucleatum is a Gram-negative anaerobic bacterium associated with periodontal disease. Some oral bacteria, like Porphyromonas gingivalis, evade the host immune response by inhibiting inflammation. On the other hand, F. nucleatum triggers inflammasome activation and release of danger-associated molecular patterns (DAMPs) in infected gingival epithelial cells.MethodsIn this study, we characterized the pro-inflammatory response to F. nucleatum oral infection in BALB/c mice. Western blots an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 78 publications
(98 reference statements)
0
21
0
Order By: Relevance
“…These results show that inflammasome activation after F. nucleatum infection is a robust but complex regulated process. In oral infection in mice, we showed that F. nucleatum induced the expression and secretion of several proinflammatory cytokines, including the inflammasome-dependent IL-1 β [130]. In agreement with in vitro and mouse model studies, the expression of the components of the NLRP3 inflammasome was also shown to be increased in periapical lesions in human subjects with periapical periodontitis [131].…”
Section: Immunological Mechanisms Triggered By P Gingivalis and Fmentioning
confidence: 63%
“…These results show that inflammasome activation after F. nucleatum infection is a robust but complex regulated process. In oral infection in mice, we showed that F. nucleatum induced the expression and secretion of several proinflammatory cytokines, including the inflammasome-dependent IL-1 β [130]. In agreement with in vitro and mouse model studies, the expression of the components of the NLRP3 inflammasome was also shown to be increased in periapical lesions in human subjects with periapical periodontitis [131].…”
Section: Immunological Mechanisms Triggered By P Gingivalis and Fmentioning
confidence: 63%
“…Uitto et al reported that F. nucleatum increase infected epithelial cell migration and survival by increasing collagenase 3 production (Uitto et al, 2005). F. nucleatum infection leads to the recruitment of macrophages and osteoclasts, finally resulting in gingival inflammation and bone resorption (Johnson et al, 2018). In human GECs, F. nucleatum upregulates the gene expression levels of IL-1, IL-6, IL-8, SOD2, CCL20, CXCL1, CXCL3, and CSF2 partly by activating the NF-κB, mitogen-activated protein kinase (MAPK) p38, and MAPK kinase/extracellular signal-regulated kinase (MEK/ERK) pathways (Huang et al, 2004;Milward et al, 2007;Ramage et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Whether such signaling is required in vivo for periodontal disease development is currently unclear, however P. gingivalis can secrete a nucleoside diphosphate kinase‐like enzyme that can remove ATP and inhibit such signaling . In addition, recent studies have begun to indicate a role for the DAMPs serum amyloid A and HMGB1 in periodontal disease, as these are increased in tissue and GCF and can activate TLR signaling in mouse models of periodontal disease . Systemic administration of anti‐HMGB1 inhibited periodontal inflammation and bone loss in a bacterial induced murine model, highlighting a potential role in periodontal progression …”
Section: Periodontal Diseasementioning
confidence: 99%